Rezatapopt: A promising small-molecule “refolder” specific for TP53Y220C mutant tumors - Kostas A. Papavassiliou; Alice G. Vassiliou; Athanasios G. Papavassiliou (Neoplasia: An International Journal for Oncology Research)
Inactivation of p53 due to mutation is observed in approximately half of all human cancer cases, therefore, restoration of the tumor suppressor function of oncogenic p53 mutants represents an attractive and rational therapeutic approach. Currently, multiple mutant p53 reactivators have been developed, but only a handful have entered clinical trials [1]. PC14586 (rezatapopt) is an orally available small-molecule reactivator of the Y220C-mutant p53 protein that showed preliminary efficacy and a favorable safety profile in a phase I clinical trial [2] and is now undergoing evaluation in a phase II clinical trial in patients with advanced solid tumors harboring the TP53Y220C mutation (NCT04585750). Although rezatapopt and other p53 mutant reactivators are under clinical assessment, there are still many knowledge gaps that need to be filled to unleash their full therapeutic potential.The preclinical data presented in a recently published research article by Puzio-Kuter et al. achieve to enhance our understanding of the mechanisms and effects of p53-Y220C reactivator compounds and underscore the potential of targeting p53 mutants in cancer therapy [3]. Through this spotlight article, we aim to summarize the findings and emphasize the clinical implications of the study by Puzio-Kutler et al.